The role of social capital in developing the character of students in SMPN 1 Lemahabang, Cirebon Regency - Majid, Abdul; Atmaja, Hamdan Tri; Mustofa, Moh. Solehatul (Universitas Negeri Semarang, 2024)
Character problems such as lack of discipline, acts of violence, deviant behavior often occur among students. Social capital owned by schools is one of the solutions to the character problems of students. The purpose of this study is to examine the development of students' character, the development of habituation, and the use of school social capital on the character of students. This research uses a qualitative approach. The research informant is the principal, teacher and parent. Informant selection techniques using purposive sampling techniques. Data collection techniques include observation, interviews and documentation. Data validity techniques through data sources triangulation. The results showed that the development of the character of students through the process of learning activities, extracurricular activities, and involving the role of parents. Development of habituation through the inculcation of cultural values, teacher capacity building programs and in the implementation of the curriculum. Social capital owned is trust, network and norms. The results of this study can be an input or suggestion for other schools regarding the role of social capital in developing the character of students by utilizing the social capital owned by the school.